Aminoglycoside induces RIPOR2 translocation and phosphatidylserine externalization via distinct mechanisms - Li, Jinan; Yang, Michelle; Zhao, Bo (Frontiers in Cellular Neuroscience, 2025)
Aminoglycosides are widely used to treat severe infections. However, systemically administered AGs preferentially kill cochlear hair cells, resulting in irreversible hearing loss. Recently, we found that AGs induce a rapid translocation of RIPOR2 in hair cells, a process that relies on functional mechanotransduction, subsequently dysregulates the autophagy/mitophagy pathway, and ultimately leads to irreversible hair cell death. Recent studies found that AGs also trigger rapid phosphatidylserine (PS) externalization in hair cells, probably by activating the scramblase activity of TMC1/2, which are the pore-forming subunits of the mechanotransduction channel. To determine whether AG-triggered rapid RIPOR2 translocation and PS externalization are independent, RIPOR2 translocation and PS externalization were extensively investigated in wild-type hair cells treated with AG for different amounts of time. Next, the potential effect of PS externalization on RIPOR2 translocation in hair cells was studied. Finally, we investigated the extent to which cisplatin, a chemotherapy drug that shares several pathological features of ototoxicity with AGs, affects PS externalization and RIPOR2 localization in hair cells. Our results suggest that AG triggers RIPOR2 translocation and PS externalization by independent mechanisms, and that cisplatin and AGs induce hair cell death via distinct molecular pathways.